Study of Students' Mathematical Communication Skills in Solving Three-Variable Linear Equation Systems - Zahra, Safa Akmalia; Arista, Sani Fauziyati; Maryono, Iyon; Rizqiyani, Rifa (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
Mathematical communication skills are essential for students to convey ideas, explain reasons, and solve mathematical problems both orally and in writing. In the context of the Three-Variable Linear Equation System (STLEV), many students face challenges in presenting solutions systematically and explaining their choice of solution methods. This study aims to analyze the mathematical communication skills of tenth-grade students in solving STLEV problems, with a focus on their arguments in choosing solution methods from both oral and written perspectives. Using a mixed-method approach with a descriptive approach, four students were purposively selected to represent diverse academic abilities. Data were collected through written exams and in-depth interviews, then analyzed using a holistic assessment rubric. Results showed variation in students’ mathematical communication skills, ranging from moderate to very high, with common difficulties including structuring solution steps and drawing conclusions. Factors such as reading habits, frequency of practice, and teacher consistency were found to influence performance. This research demonstrates the need for explicit training in systematic solution writing and reasoning to enhance conceptual understanding and problem-solving skills in mathematics.